Anatomy of the pubovisceral muscle origin: Macroscopic and microscopic findings within the injury zone. Issue 8 (22nd August 2014) - Kim, Jinyong; Betschart, Cornelia; Ramanah, Rajeev; Ashton‐Miller, James A.; DeLancey, John O. L.
<x xml:space="preserve">Abstract</x> Aims The levator ani muscle (LA) injury associated with vaginal birth occurs in a characteristic site of injury on the inner surface of the pubic bone to the pubovisceral portion of the levator ani muscle's origin. This study investigated the gross and microscopic anatomy of the pubic origin of the LA in this region. Methods Pubic origin of the levator ani muscle was examined in situ then harvested from nine female cadavers (35–98 years). A combination of targeted feature sampling and sequential sampling was used where each specimen was cut sequentially in approximately 5 mm thick slices apart in the area of known LA injury. Histological sections were stained with Masson's trichrome. Results The pubovisceral origin is transparent and thin as it attaches tangentially to the pubic periosteum, with its morphology changing from medial to lateral regions. Medially, fibers of the thick muscle belly coalesce toward multiple narrow points of bony attachment for individual fascicles. In the central portion there is an aponeurosis and the distance between muscle and periosteum is wider (∼3 mm) than in the medial region. Laterally, the LA fibers attach to the levator arch where the transition from pubovisceral muscle to the iliococcygeal muscle occurs. Conclusions The morphology of the levator ani origin varies from the medial to lateral margin. The medial origin is a rather direct attachment of the muscle, while lateral origin is made through the levator arch. Neurourol. Urodynam. 34:774–780, 2015. © 2014 Wiley Periodicals, Inc.